1985
DOI: 10.1679/aohc.48.69
|View full text |Cite
|
Sign up to set email alerts
|

Blood vascular bed of the rat pituitary intermediate lobe, with special reference to its development and portal drainage into the anterior lobe. A scanning electron microscope study of vascular casts.

Abstract: Summary. Blood vascular beds of the rat pituitary intermediate lobes were reproduced by injection of low viscosity methacrylate media, and then observed with a scanniag electron microscope. Although the intermediate lobes of newborn and pubescent rat were poorly vascularized, the adult rat intermediate lobe contained numerous capillaries forming a fairly independent network whose density, however, was not so great as in the anterior and posterior lobes. The vascular network of the intermediate lobe could be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The present paper clearly shows that our low viscosity methacrylate media are useful for completely casting all the blood vascular beds of the hypophysis and hypothalamus (MURAKAMI, 1975a, b ;MURAKAMI et al, 1984MURAKAMI et al, , 1985. Our preliminary experiments in this study have shown that the commercially available Mercox media or Batson's plastic are so viscous that they are not always suited for complete infusion into such complicated capillary networks as those of the hypophysis and hypothalamus.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The present paper clearly shows that our low viscosity methacrylate media are useful for completely casting all the blood vascular beds of the hypophysis and hypothalamus (MURAKAMI, 1975a, b ;MURAKAMI et al, 1984MURAKAMI et al, , 1985. Our preliminary experiments in this study have shown that the commercially available Mercox media or Batson's plastic are so viscous that they are not always suited for complete infusion into such complicated capillary networks as those of the hypophysis and hypothalamus.…”
Section: Discussionmentioning
confidence: 72%
“…Some authors have claimed that the communications originate in the capillaries of the primary plexus, and thus regard them as a possible feed-back portal route from the hypophysis to the hypothalamus (BASIR, 1932;TOROK, 1960TOROK, , 1964BERGLAND and PAGE, 1979), others have maintained that they arise directry from the arterial branches in the primary plexus to supply the hypothalamic capillaries (DUVERNOY, 1972). Our previous studies by dissection/scanning electron microscopy of the methacrylate vascular casts of the monkey, dog and rat have supported the latter view of the arterial origin (MURAKAMI,1975a, b ;KIKUTA et al, 1984;MURAKAMI et al, 1985).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In mice, MC3-R mRNA is localized in most mammotrophs and some somatotrophs . Blood from the rat intermediate lobe to the anterior lobe flows through the portal link between the vascular network of the intermediate lobe and the sinusoidal capillaries of the anterior pituitary (Murakami et al, 1985). α-MSH released from the intermediate lobe can therefore reach mammotrophs in the anterior pituitary and stimulate PRL release and cell proliferation.…”
Section: Proopiomelanocortin (Pomc) Peptidesmentioning
confidence: 99%
“…Recently, a scanning electron microscope study of cast samples of the rat pituitary gland suggested that the capillary bed of the rat pars intermedia is a fairly independent unit, and a constant portal drainage system into the pars distalis (Murakami et al, 1985). The pars intermedia of the newborn rat pituitary gland is poorly vasculated.…”
Section: Vasculature Of the Pars Intermediamentioning
confidence: 99%